Ebola, jobs and economic activity in Liberia. Issue 3 (5th October 2015) - Bowles, Jeremy; Hjort, Jonas; Melvin, Timothy; Werker, Eric
Abstract : Background: The 2014 Ebola virus disease (EVD) outbreak in the neighbouring West African countries of Guinea, Liberia and Sierra Leone represents the most significant setback to the region's development in over a decade. This study provides evidence on the extent to which economic activity declined and jobs disappeared in Liberia during the outbreak. Methods: To estimate how the level of activity and number of jobs in a given set of firms changed during the outbreak, we use a unique panel data set of registered firms surveyed by the business-development non-profit organisation, Building Markets. We also compare the change in economic activity during the outbreak, across regions of the country that had more versus fewer Ebola cases in a difference-in-differences approach. Findings: We find a large decrease in economic activity and jobs in all of Liberia during the Ebola outbreak, and an especially large decline in Monrovia. Outside of Monrovia, the restaurants, and food and beverages sectors have suffered the most among the surveyed sectors, and in Monrovia, the construction and restaurant sectors have shed the most employees, while the food and beverages sectors experienced the largest drop in new contracts. We find little association between the incidence of Ebola cases and declines in economic activity outside of Monrovia. Conclusions: If the large decline in economic activity that occurred during the Ebola outbreak persists, a focus on economic recovery may need to be added to the efforts to rebuild and support the healthcare system in order for Liberia to regain its footing.